The ECG made easy for the dental practitioner - U R Anoop; Ramesh; Kavita Verma; Narayanan (Wolters Kluwer Medknow Publications, 2014)
ECG is not taught to dental students formally in the dental curriculum. The general assumption is that dental surgeons do not handle any ECG related cases in clinical practice. But with an increase in medically compromised patients, the need for an interdisciplinary approach among dental and medical practitioners in the treatment of critically ill patients is becoming more relevant. Hence, we have to be aware of the basics of common medical investigations to be competent to assess and comprehend the medical conditions. So, this paper focuses on orienting the beginner to the basic concepts of ECG from the clinical perspective. The paper also discusses the ECG changes of myocardial infarction to familiarize the dental surgeon to read the ECG.